Nominally acceptable integrity failures negatively affect interventions involving intermittent reinforcement. Issue 4 (12th July 2022) - Jones, Stephanie H.; St. Peter, Claire C.
Abstract : The finding that differential reinforcement of alternative behavior (DRA) is efficacious at 80% integrity when continuous reinforcement is programmed for alternative responding may have contributed to a perception that integrity at 80% or above is acceptable. However, research also suggests that other interventions (e.g., noncontingent reinforcement) may not remain effective at 80% integrity. The conditions under which 80% integrity is acceptable for common behavioral interventions remains unclear. Therefore, we conducted two human‐operant studies to evaluate effects of 80% integrity for interventions with contingent or noncontingent intermittent reinforcement schedules. During Experiment 1, we compared noncontingent reinforcement (NCR) and DRA when implemented with 80% integrity. During Experiment 2, we compared 2 variations of DRA, which included either a ratio or interval schedule to reinforce alternative behavior. Results replicated previous research showing that DRA with a FR‐1 schedule programmed for alternative responding resulted in consistent target response suppression, even when integrity was reduced to 80%. In contrast, neither NCR nor interval‐based DRA were consistently effective when implemented at 80% integrity. These results demonstrate that 80% integrity is not a uniformly acceptable minimal level of integrity.